Genetic variability, correlation and path analysis for yield and its contributing traits in Barley (Hordeum vulgar L.) (SAARC Journal of Agriculture, 2023)
In breeding programs, direct selection based on crop yields is paradoxical due to its complex polygenically inherited nature, that is impacted by its component traits. To determine the degree of relationship between yield and yield components and other traits in nine barley varieties, a field experiment was carried out at the Regional Agricultural Research Station, Jashore during Rabi 2021–2022. For plant height, disease and insect reaction, and grain yield, substantial heritability together with strong genetic progress as a percentage of mean were detected, indicating a prevalence of additive gene action in the expression of these traits. At both the genotypic and phenotypic levels, the correlation coefficient between grain yield was shown to be positively correlated with plant height and thousand grain weight, indicating that an increase in these traits will boost grain production. Both genotypic and phenotypic analysis of the path coefficient demonstrated that plant height and thousand grain weight had a direct positive impact on grain production, highlighting the significance of these parameters as the primary contributors to yield. For the purpose of genetically improving barley yield, a genotype with a higher extent of these qualities could be chosen as a parent from among genotypes that already exist.SAARC J. Agric., 21(2): 15-25 (2023)